The Identity of the Russian Federation in the Framework of the Presidential Addresses to the Federal Assembly - V. G. Tikhonov (Евразийская интеграция: экономика, право, политика, 2021)
The article is based on content and discourse analysis of the addresses of the President of the Russian Federation to the Federal Assembly dated 12/01/2016, 03/01/2018, 02/20/2019, 01/15/2020. The aim of research is to analyze the concept of identity in the framework of Presidential Addresses and changes in the concepts of identity in dynamics. The general tendencies of considering the term “identity” in the framework of determining the identity of the Russian Federation are derived. The special relationship between the identity of the Russian Federation and the integration of the Russian Federation into integration spaces is considered. The Vladimir Putin’s statements regarding the integration of the Russian Federation into the Eurasian Economic Union are evaluated, since the Russian Federation identity, in the opinion of the President, is inextricably linked with the formation of the “Eurasian identity of the Russian Federation”, which in turn determines the direct relationship between the identity of the Russian Federation and the integration of the Russian Federation into the Eurasian Economic Union. The article defines the subjective factor of the Russian President, which reflects the personal nature of the President’s orders and proposals. The dynamics of changes in the formation of the Russian Federation identity is reflected according to the addresses of the President of the Russian Federation to the Federal Assembly, and also on the basis of the dynamics of changes in the identity of the Russian Federation, the general process orientation of developing the Russian Federation identity is reflected. The article characterizes the permanent nature of the formation of the identity of Russia. Now, the identity of Russia is perceived as a special construct that reflects the special position of the Russian Federation, both in historical development and in the international arena.